To the Critisism of Views Expressed in the Separatist Historiography Regarding the Ethnic, Cultural, Political and State Character of the Abkhaz Kingdom - Papaskiri, Zurab (Actual Problems of Kartvelology, 2025)
The authors analyzed in the work are trying in every way to convince the whole world that the "Abkhazian" kingdom created by Leo II at the end of the 8th century, which for at least two centuries (until Bagrat III assumed the title of "King of the Georgians") represented only the Abkhazian national state. Of course, other publications could be cited in which this opinion is replicated, but we believe that the material provided is quite sufficient to show the historiographical confusion in which our Abkhaz colleagues are placing their compatriots. Georgian historiography has quite convincingly demonstrated the complete absurdity of the Abkhazian (separatist) vision of the national-state form of the "Abkhazian" kingdom and has clearly explained why the political union bearing the name of the "Abkhazian" kingdom cannot be considered an Abkhazian-Abkhazian national-state and why it represents only and exclusively a Georgian national-state union.